2022
DOI: 10.1038/s41467-022-30228-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome editing in animals with minimal PAM CRISPR-Cas9 enzymes

Abstract: The requirement for Cas nucleases to recognize a specific PAM is a major restriction for genome editing. SpCas9 variants SpG and SpRY, recognizing NGN and NRN PAMs, respectively, have contributed to increase the number of editable genomic sites in cell cultures and plants. However, their use has not been demonstrated in animals. Here we study the nuclease activity of SpG and SpRY by targeting 40 sites in zebrafish and C. elegans. Delivered as mRNA-gRNA or ribonucleoprotein (RNP) complexes, SpG and SpRY were ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Based on our results, we conclude that CBE technology is a more efficient, easier to design, and time-saving approach to introduce a specific C:G to T:A mutation into the genome and should be considered as an alternative for prime editing and HDR-based knock-in techniques. Moreover, while our manuscript was under review, the Cas9-SpRY has been shown to be efficient for classical knock-out approaches generating INDELS in zebrafish 39 . The use of the CBE4max-SpRY is expected to increase the number of potential off-targets compared to the classical base editors as it is highly flexible on the type of PAM used; however, the NGS analyses revealed a good fidelity of the CBE4max-SpRY.Indeed, the presence of only one mismatch on the off-target site decreases drastically the efficiency of base editing and for the other analyzed off-targets no mutations were detected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we conclude that CBE technology is a more efficient, easier to design, and time-saving approach to introduce a specific C:G to T:A mutation into the genome and should be considered as an alternative for prime editing and HDR-based knock-in techniques. Moreover, while our manuscript was under review, the Cas9-SpRY has been shown to be efficient for classical knock-out approaches generating INDELS in zebrafish 39 . The use of the CBE4max-SpRY is expected to increase the number of potential off-targets compared to the classical base editors as it is highly flexible on the type of PAM used; however, the NGS analyses revealed a good fidelity of the CBE4max-SpRY.Indeed, the presence of only one mismatch on the off-target site decreases drastically the efficiency of base editing and for the other analyzed off-targets no mutations were detected (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, several optimization strategies can be considered to limit off-target effects, such as alteration of the crRNA and optimizing Cas9 concentrations [ 29 ]. While a PAM needs to be directly adjacent to the intended cleavage site to allow CRISPR-mediated editing [ 28 ], due to the variety in naturally occurring Cas-proteins and Cas-proteins with mutations in the PAM-recognition domain, a variety in PAM sequences is available to facilitate gene targeting [ 28 , 48 , 49 , 50 ]. As a result, virtually any gene or DNA region of interest can be targeted with the CRISPR system, in contrast to other gene editing tools such as ZFNs [ 30 ].…”
Section: Gene Editing Basics—mode Of Action and Different Toolsmentioning
confidence: 99%
“…adjacent to the intended cleavage site to allow CRISPR-mediated editing [28], due to the variety in naturally occurring Cas-proteins and Cas-proteins with mutations in the PAMrecognition domain, a variety in PAM sequences is available to facilitate gene targeting [28,[48][49][50]. As a result, virtually any gene or DNA region of interest can be targeted with the CRISPR system, in contrast to other gene editing tools such as ZFNs [30].…”
Section: Gene Editing Basics-mode Of Action and Different Toolsmentioning
confidence: 99%
“…VQR recognizes NGAG as efficiently as wild-type Cas9 targets NGG [17], thus broadening the range of targets. Additionally, SpG and SpRY are two modified versions of Cas9 with more relaxed PAM requirements than Cas9 [18]. Thus, they target more portions of the genome.…”
Section: Cas9 Variantsmentioning
confidence: 99%